2006
DOI: 10.3102/00346543076001093
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Courses Online: A Review of the Research

Abstract: This literature review summarizes research on online teaching and learning. It is organized into four topics: course environment, learners' outcomes, learners' characteristics, and institutional and administrative factors. The authors found little consistency of terminology, discovered some conclusive guidelines, and identified developing lines of inquiry. The conclusions overall suggest that most of the studies reviewed were descriptive and exploratory, that most online students are nontraditional and Anglo A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
463
0
16

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 846 publications
(540 citation statements)
references
References 61 publications
12
463
0
16
Order By: Relevance
“…Having more time to respond online than in a traditional classroom context may increase student motivation and participation, especially in shy students (Spodark, 2001). In a review of 76 articles concerning online study, one group of researchers concluded that, despite self-management challenges, students prefer to study at their own paces, and that convenience and student autonomy were two benefits of online study (Tallent-Runnels, Thomas, Lan, Cooper, Ahern, Shaw, & Liu, 2006). Time to reflect on materials before responding was also a benefit cited by researchers in distance learning (Matthews, 1999;Simonson, Smaldino & Zvacek, 2000;Aharony, 2011).…”
Section: Student Perception and Satisfaction With Online Lessonsmentioning
confidence: 99%
“…Having more time to respond online than in a traditional classroom context may increase student motivation and participation, especially in shy students (Spodark, 2001). In a review of 76 articles concerning online study, one group of researchers concluded that, despite self-management challenges, students prefer to study at their own paces, and that convenience and student autonomy were two benefits of online study (Tallent-Runnels, Thomas, Lan, Cooper, Ahern, Shaw, & Liu, 2006). Time to reflect on materials before responding was also a benefit cited by researchers in distance learning (Matthews, 1999;Simonson, Smaldino & Zvacek, 2000;Aharony, 2011).…”
Section: Student Perception and Satisfaction With Online Lessonsmentioning
confidence: 99%
“…According to Silva and Campos (2016); Formiga and Marcos (2004); Litto and Formiga (2008) and Silva and Behr (2016), distance education can be divided into three generations according to the growth of new means of communication: 1 st generation -teaching by correspondence; 2 nd generation -teaching by computer and printed media related to tele-education; and 3 rd generation -virtual or e-learning. What these generations have in common is a lack of space-time limits.…”
Section: Characteristics Of Distance Education In Brazil and The Worldmentioning
confidence: 99%
“…According to Tallent-Runnels (2006) there are three models of education: 1) online education -a course of study conducted entirely through the internet; 2) traditional education (face-to-face) -a course of study conducted entirely in-person and 3) hybrid education -a course of study partially conducted in-person and partially through the internet. According to the MEC there are two types of study recognized in Brazil: in-person and distance.…”
Section: Characteristics Of Distance Education In Brazil and The Worldmentioning
confidence: 99%
“…In the USA, as early as in the academic year 2000-2001, 90% of public 2-year and 89% of public 4-year institutions offered distance education courses, not to mention that almost three millions individuals were earning credits at college-level via online courses [41]. Social media as well, while not being specifically aimed at didactic activities, attracted the attention of teachers and students: in the USA, more than 60% of the faculties include social media in their teaching practices, whether this means to deliver content through social networking platforms (30% of the teachers) or to require access to social media in order to complete assessed exercises (40% of the teachers) [24].…”
Section: Introductionmentioning
confidence: 99%